Effect of Participation in Village Savings and Loans Associations on the Financial Performance of Rural Households in Northern Region, Ghana - Munkaila, Lambongang; Awoyemi, Abiodun Emmanuel; Sokpor, Kafui Kosiwor (International Journal of Publication and Social Studies, 2020)
It is always important to evaluate the performance of interventions that can help in the financial inclusion of rural households since most are excluded in the formal financial sector due to collateral requirements. This paper examined the effect of participation in VSLA (village savings and loan associations) programme on the financial performance of rural households in the Northern region of Ghana. Data from a cross-section of rural farmers were analyzed using the Heckman treatment effects model. The results showed that participants in the VSLA programme had better financial performance than the non-participants by about GH₵ 457.239 per month. However, farmers mentioned critical challenges to include absenteeism to meetings, the poor database in terms of contributions and disbursement as the major challenges obstructing their progress. Therefore, the government through the district assemblies as well as concern NGOs that are interested in rural development should step in to help enhance their operations. Finally, absenteeism should be made a disincentive to the participants through the payment of some fines when one fails to attend a meeting without a genuine reason.